Preaching Rhetoric and Friday Sermon Training for KPI Department students at UIN Datokarama and Mosque Takmir - Cikka, Hairuddin; Adam, Adam; Hidayat, Mokh. Ulil; Alimuddin, Nurwahidah; Sabir, M. (Universitas Pahlawan Tuanku Tambusai, 2026)
The Friday sermon and preaching rhetoric training program increased knowledge and understanding of the role of the imam and preacher in Friday prayers. This was demonstrated by the training's ability to improve participants' understanding of the etiquette of an imam and preacher, the pillars, requirements, and sunnah of a preacher, sermon preparation, Quranic recitation, and preaching rhetoric and performance during sermon delivery. Furthermore, and importantly, participants were able to select lecture and sermon content that aligns with moderate Islamic teachings and fosters national insight.